2015
DOI: 10.1111/echo.12973
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Right Ventricular Shape and Deformation Following Coronary Artery Bypass Surgery—Insights from Echocardiography with Strain Rate and Magnetic Resonance Imaging

Abstract: Post-CABG longitudinal motion of the RV lateral wall is reduced after uneventful CABG despite preserved RV ejection fraction and stroke volume. The discrepancy in various RV systolic performance indicators results from increased sphericity of the RV following opening the pericardium during surgery. Therefore, longitudinal functional parameters may underestimate RV systolic function for at least 8-10 months post-CABG. Changes in deformation parameters should thus always be interpreted in relation to changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
6
25
0
1
Order By: Relevance
“…It is often incised during CABG and not sutured after the surgery, and previous studies have found RV systolic function decreased postoperatively. Intraoperative studies suggested that the reduction occurred immediately after pericardial opening and persisted throughout the surgery, which indicated that pericardial incision induced change in RV geometry and the contractile pattern [7,[15][16][17]. In the current study, we also noted that the right ventricle had increased sphericity despite the unchanged RV fractional area change immediately after pericardial incision.…”
Section: Discussionsupporting
confidence: 66%
“…It is often incised during CABG and not sutured after the surgery, and previous studies have found RV systolic function decreased postoperatively. Intraoperative studies suggested that the reduction occurred immediately after pericardial opening and persisted throughout the surgery, which indicated that pericardial incision induced change in RV geometry and the contractile pattern [7,[15][16][17]. In the current study, we also noted that the right ventricle had increased sphericity despite the unchanged RV fractional area change immediately after pericardial incision.…”
Section: Discussionsupporting
confidence: 66%
“…[8][9][10] Furthermore, depressed longitudinal function may persist for one year or more despite a successful and otherwise uncomplicated clinical course. 3,5,[11][12][13] Proposed mechanisms for this observation include the loss of pericardial support consequent to the necessary pericardiotomy for cardiac surgery, ischemic injury to the right ventricle (RV) due to incomplete myocardial protection, or formation of adhesions between the RV and the surrounding tissues, all of which could then alter RV geometry and contraction patterns.…”
Section: Résumémentioning
confidence: 99%
“…Thus, following CABG, nearly all patients had at least two hypokinetic segments at rest (WMS 85%, PLS 95%, PLSR 96%). Post‐CABG strain in different walls and segments was equally reduced not being influenced by the known post‐CABG changes in septal transversal motion . Prevalence of ischemia‐positive and ischemia‐negative segments in each patient are displayed in Table .…”
Section: Resultsmentioning
confidence: 98%
“…The study was designed as a prospective cohort study. Data from the same patient population have previously been published, investigating different aspects of viability testing and changes in right ventricle (RV) function post‐CABG . Our previous studies have addressed a low‐dose dobutamine stress test and late gadolinium enhancement (LGE) by CMR for viability assessment, as well as for assessing RV geometry, pressure and functional measures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation